Pengembangan Kurikulum Dalam Pembelajaran Pendidikan Islam Kelas III SD Islam Terpadu Ananda Prabumulih Tahun 2023/2024 - Hoirotul Hasanah; Mustafiyanti Mustafiyanti (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Curriculum development at SDIT Ananda Prabumulih is important to study from various perspectives. This study will discuss two fundamental aspects of basic curriculum development and curriculum objectives. A discussion of the literature reveals that the curriculum provided by schools is not only limited to subject units and teaching and learning processes but also to all processes that influence the development and formation of students' character as required by national education goals. Curriculum development aims to adapt education and social change and explore untapped knowledge. The curriculum is one of the most crucial components in an education system, therefore the curriculum is a tool for achieving educational goals and at the same time as a guideline in the implementation of teaching at the initial type and level of education. In Islam, the concept of curriculum means manhaj, namely the clear path traversed by educators and their students to develop their knowledge, skills and attitudes. Islamic education curriculum is Islamic educational materials in the form of activities, knowledge and experiences that are deliberately and systematically given to students. in order to achieve the goals of Islamic education.